Quintuple Helix Dalam Peningkatan Potensi Lokal Berbasis Ekonomi Biru Pelabuhan Kota Probolinggo - Fitria, Nurul Jannah Lailatul; Sucahyo, Imam; Supriyanto, Supriyanto (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
Indonesia is a maritime country. Indonesia optimizes its maritime potential relevant to the country's goal as a world maritime axis. Maritime development is oriented toward the five pillars of the world maritime axis: maritime culture, economy, connectivity, diplomacy, and security. This can be realized in Indonesian policies, including the blue economy policy. Increasing relevant local potential in the blue economy at the port of Probolinggo City involves various parties. Researchers are interested in researching the quintuple Helix (QuiH), orienting the Probolinggo City Port environment with blue economy principles. The research applied a qualitative method with a case study approach. The research locus is in the Probolinggo City Port area. This research shows the quintuple helix innovation model in developing Probolinggo City Port with blue economy principles. The quintuple helix model in the Probolinggo City Port Complex describes that the innovation flow is driven by the role of the main helixes/subsystems of innovation, namely academics, the Probolinggo City Government, business actors, the Probolinggo City community, and the natural environment of the port in Probolinggo City. Technically, the role of each helix is very diverse; not all helixes have the same portion of the role, and not all helixes play a role as producers of innovation.